High Concentration or Combined Treatment of Antisense Oligonucleotides for Spinal Muscular Atrophy Perturbed SMN2 Splicing in Patient Fibroblasts - Wijaya, Yogik Onky Silvana; Niba, Emma Tabe Eko; Nishio, Hisahide; Okamoto, Kentaro; Awano, Hiroyuki; Saito, Toshio; Takeshima, Yasuhiro; Shinohara, Masakazu (MDPI, 2022)
Spinal muscular atrophy (SMA) is caused by survival motor neuron 1 SMN1 deletion. The survival motor neuron 2 (SMN2) encodes the same protein as SMN1 does, but it has a splicing defect of exon 7. Some antisense oligonucleotides (ASOs) have been proven to correct this defect. One of these, nusinersen, is effective in SMA‐affected infants, but not as much so in advanced‐stage pa-tients. Furthermore, the current regimen may exhibit a ceiling effect. To overcome these problems, high‐dose ASOs or combined ASOs have been explored. Here, using SMA fibroblasts, we examined the effects of high‐concentration ASOs and of combining two ASOs. Three ASOs were examined: one targeting intronic splicing suppressor site N1 (ISS‐N1) in intron 7, and two others targeting the 3′ splice site and 5′ region of exon 8. In our experiments on all ASO types, a low or intermediate concentration (50 or 100 nM) showed better splicing efficiency than a high concentration (200 nM). In addition, a high concentration of each ASO created a cryptic exon in exon 6. When a mixture of two different ASOs (100 nM each) was added to the cells, the cryptic exon was included in the mRNA. In conclusion, ASOs at a high concentration or used in combination may show less splicing correction and cryptic exon creation.